The effect of Ramadan weight loss on body composition of overweight and obese Muslims in University Putra Malaysia - Ismail, Suriani; Shamsuddin, Khadijah; Abdul Latif, Khalib; Abu Saad, Hazizi; Mohd Othman, Fadlan (Community Health Society Malaysia, 2015)
Introduction: During Ramadan Muslims fast for a month and most research have reported significant decrease in weight and body mass index (BMI). The objective of this study was to observe the body composition changes in the decreased BMI during Ramadan fasting among a group of overweight and obese Muslims.